Music as creative practice - Cook, Nicholas 1950- (Studies in musical performance as creative practice, 2018)
Until recently, ideas of creativity in music revolved around composers in garrets and the lone genius. But the last decade has witnessed a sea change: musical creativity is now overwhelmingly thought of in terms of collaboration and real-time performance. Music as Creative Practice is a first attempt to synthesize both perspectives. It begins by developing the idea that creativity arises out of social interaction-of which making music together is perhaps the clearest possible illustration-and then shows how the same thinking can be applied to the ostensively solitary practices of composition. The book also emphasizes the contextual dimensions of musical creativity, ranging from the prodigy phenomenon, long-term collaborative relationships within and beyond the family, and creative learning to the copyright system that is supposed to incentivize creativity but is widely seen as inhibiting it. Music as Creative Practice encompasses the classical tradition, jazz and popular music, and music emerges as an arena in which changing concepts of creativity-from the old myths about genius to present-day sociocultural theory-can be traced with particular clarity. The perspective of creativity tells us much about music, but the reverse is also true, and this fifth and last instalment of the Studies in Musical Performance as Creative Practice series offers an approach to musical creativity that is attuned to the practices of both music and everyday life. - Nicholas Cook is Emeritus Professor of Music at the University of Cambridge and a Fellow of the British Academy. His book Music: A Very Short Introduction (1998) has been translated into seventeen languages, and his The Schenker Project (2007) won the Society for Music Theory's Wallace Berry Award. His most recent monograph is Beyond the Score: Music as Performance (2013).